The Evaluation of New Roundabout Performance: A Case Study of Barelang Roundabout Development - Andika, Ilham; Rifai, Andri Irfan; Djamal, Endry Z. (DAS Institute, 2022)
Smooth traffic conditions can improve population mobility services and other supporting resources for economic growth. However, traffic jams often occur in a densely populated city like Batam, which stress road users, improve economic speed, and waste much time. Therefore, it is necessary to check the steering performance. The purpose of this study is to determine whether the Barelang junction roundabout is effective in the traffic situation prevailing in the area. In this study, a traffic survey was conducted on the Barelang Junction Batam road to determine the number of vehicles passing through Barelang Junction. The reference used in this research is the Indonesian Highway Capacity Manual (IHCM) 1997, where road capacity, traffic density, and saturation level are analyzed. The results obtained from SP Plaza to the road to Muka Kuning have a saturation value of 0.72. The saturation level of the route from Muka Kuning to SP Plaza is 0.57. Based on IHCM 1997, it was determined that the value of the saturation level of a road section should not be more than 0.75, so it can be concluded that the two roads located at the Barelang T-junction are classified as efficient. The results of this study can be used as a benchmark to improve transportation performance.